Analysis on Ethical Issues Raised by Technology and the Path of Prevention (Asian Journal of Social Science Studies, 2022)
The ethics of science and technology is a hot direction that needs urgent attention in the study of philosophy of science and technology. This paper first analyzes the ethical problems caused by science and technology in four dimensions (individuals, human interaction, human-nature relationship, and social governance), and argues that the essence of these ethical problems is that human equality, freedom, and value judgment are violated, human subjective feelings are ignored, and the harmonious and natural relationship between human and others is impacted. Secondly, this paper discusses the prevention path for ethical problems caused by science and technology, arguing that: firstly, it should be clear that the preventive path to be taken needs to be comprehensive, flexible and people-oriented; secondly, it should take national guidance and supervision as the core to provide principled and rigid constraints; thirdly, it should take social self-regulation as a supplement to make concrete and soft self-discipline; finally, all countries should utilize global power to standardize ethical principles and jointly resist technological risks.